Self-report assessment of cognitive ability and academic achievement in higher education - Mohd. Kosnin, Azlina (Penerbit UTM, 2008)
Self-report is a form of measurement which requires subjects to fill out a questionnaire or answer a series of questions. Self-report assessment of cognitive ability involves reflecting on past achievements, critically evaluating present performance and planning future goals (McAlpine, 2000). Items would cover overt (actions) as well as covert (cognition and conation) behaviours. Three different selfreport assessment formats have been used (Harrington, 1995). These can take the form of a listing of abilities with definitions and directions to indicate best or strongest areas, a Likert scale for a group of abilities, or different examples of applications of ability on which individuals rate their performance level from high to low. Compared to intelligence tests, self-report data is economical, easy to collect and easy to work with. Although the use of self-report has a long history in educational and psychological practice and research, its use to measure cognitive ability is quite new, as intelligence tests have for many years dominated the field of ability measurement. Reasons for the interest in self-report assessment of cognitive ability in education can be seen from two perspectives. Firstly, researchers may be interested to see whether self-report assessment can be used as proxy for an intelligence test. If this could be proven, self-report would be of immense value and could be used as an economical alternative for intelligence testing. Secondly, practitioners, especially educators and counsellors are aware of some of the negative impacts IQ tests may have on students. Self-report assessment of ability has been introduced to help people become aware of and develop their ability and talents.